Analisis Pengaruh PMDN & PMA Terhadap PDRB di Kabupaten Siak - Windi Wardani; Sri Endang Kornita; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in Siak Riau province, to determine the effect of Domestic Investment (DCI)  and the Foreign Investment (FDI) to GDP in Siak, and to find out how it contribution to GDP in Siak. In analyzing the authors use quantitative methods, to determine the effect of variables FDI and domestic investment partially and simultaneously on employment Siak, years 2003-2012 with the technique of multiple linear regression analysis. The results showed that domestic and foreign, have a significant  influence on the Siak GDP in 2003-2012 to 77.1 % influence. Obtain partial test results that are positive and significant effect of FDI to GDP  Siak years  2003-2012. While domestic investment and a significant negative effect on GDP Siak years 2003-2012. Average ICOR PMA Siak from year 2003-2012 amounted to 3.1171 and the average ICOR of domestic capital in the Siak years 2003-2012 amounted to 4.9258. While the average investment in Siak regency ICOR of  the year 2003-2012 amounted  to 8.0428. The ICOR value meant that the use of domestic and foreign  investment in 2003-2012 is not fully efficient. This means that the investment can not be used to the fullest and not fully included in the government wisdom supported by investment.Keywords: PMA, PMDN, ICOR.